Understanding Interactive Legends: a Comparative Study with Standard Widgets - Henry Riche, Nathalie; Lee, Bongshin; Plaisant, Catherine (In Proceedings of EuroVis 2010 (Computer Graphics Forum), 2010)
Interactive information visualization systems rely on widgets to allow users to interact with the data and modify the representation. We define interactive legends as a class of controls combining the visual representation of static legends and interaction mechanisms of widgets. As interactive legends start to appear in popular websites, we categorize their designs for common data types, and evaluate their effectiveness compare to standard widgets. Results suggest that 1) interactive legends can lead to faster perception of the mapping between data values and visual encodings and 2) interaction time is affected differently depending on the data type. Additionally, our study indicates superiority both in terms of perception and interaction of ordinal controls over numerical ones. Numerical techniques are mostly used in today’s systems. By providing solutions to allowing users to modify ranges interactively, we believe that interactive legends make it possible to increase the use of ordinal techniques for visual exploration.